EFEKTIVITAS DIABETES SELF MANAGEMENT EDUCATION DAN COMMUNITY BASED INTERACTIVE APPROACH TERHADAP SELF CARE PENDERITA DIABETES MELLITUS - Diani Novianti; Nina Indriyawati; Syamsul Arif Setyonegoro (Poltekkes Kemenkes Semarang, 2019)
Background: Self care deficit is still a major problem in patients with type 2 diabetes mellitus because self care agency is lower than self care demands, where it can be influenced by several factors, one of which is knowledge.Purpose: This study aims to determine the effectiveness of DSME and CBIA-DM on self care in people with diabetes mellitus.Methods: The research method was quasy prepost test design. Sample of the study was diabetes mellitus type 2 patients (n=52) divided into 2 groups using non probability sampling with purposive sampling. The instrument used SDSCA questionnaire by Kusniawati (2011) (r = 0,361, alpha cronbach ‘s = 0,80). Data analysis used dependent and independent t test.Results: Data analysis used independent t test obtained p value 0.019, indicating there was a significant differences and the results of the Δmean DSME group was 18,50 and the Δmean CBIA-DM group was 15.61, so that DSME was more effective than CBIA-DM.Conclusion: DSME is more effective to improving self care in people with diabetes mellitus. It is recommended that the Puskesmas can implement the DSME intervention conducting socialization through prolanist activities.